Physiological responses to honeybee venom poisoning in a model organism, the firebug Pyrrhocoris apterus - Ondřichová, Anna; Štěrbová, Helena; Danihlík, Jiří; Jemelková, Jana; Hejníková, Markéta; Šerý, Michal; Kodrík, Dalibor (Comparative biochemistry and physiology. Toxicology & pharmacology, 2023)
In this study, the biochemical and physiological features of the firebug Pyrrhocoris apterus were investigated to understand the impact of the honeybee Apis mellifera venom on them using physiological methods (mortality, total level of metabolism), biochemical methods (ELISA, mass spectrometry, polyacrylamide gel electrophoresis, spectrophotometry) and molecular methods (real-time PCR). Together, the obtained findings suggest that venom injection increased the level of adipokinetic hormone (AKH) in the CNS of P. apterus, indicating that this hormone plays a key role in activating defence responses. Furthermore, histamine levels in the gut increased significantly after envenomation and did not seem to be modulated by AKH. In contrast, histamine levels in the haemolymph increased after treatment with AKH and AKH + venom. In addition, we found that vitellogenin levels in haemolymph decreased in both males and females after venom application. Lipids, which are the main energy metabolites used by Pyrrhocoris, were significantly exhausted from the haemolymph after the administration of venom and the co-application with AKH reversed this effect. However, we did not find much influence on the effect of digestive enzymes after the injection of venom. Our research has highlighted the noticeable effect of bee venom on P. apterus' body and provided new insights into the role of AKH in controlling defensive responses. However, it is also likely that there will be alternative defence mechanisms.
Keywords: Bee venom; Male; Stress; včelí jedy; hmyzí hormony; mužské pohlaví; kyselina pyrrolidonkarboxylová; Histamine; Bee Venoms; Pyrrolidonecarboxylic Acid; histamin; Adipokinetic hormone; Animals; ženské pohlaví; zvířata; Insect Hormones; Metabolism; Female; Heteroptera